Aging study of linseed oil resin/styrene thermosets and their composites with wood flour - Mosiewicki, Mirna Alejandra (2007)
The changes in the properties of new crosslinked polymers based on renewable resources and their derived composites have been monitored as a function of time; this knowledge being necessary to estimate their behavior in final applications. Rigid thermoset polymers prepared by free radical polymerization of resins obtained from linseed oil and styrene and composites reinforced with wood flour were evaluated in different environmental conditions and at different times after their preparation. The action of atmospheric oxygen on the unsaturated groups in fatty acids produces chemical changes in these polymers, which affect the properties of the cured materials. These changes were analyzed using Fourier transform infrared spectroscopy, dynamic mechanical analysis and mechanical testing. An increase in the modulus with time was observed during exposure of the samples to dry conditions, or humid environments (60% relative humidity), with or without UV irradiation. The reaction with oxygen appears to be accelerated when the materials are subjected to UV irradiation, showing a large effect on the glass transition temperature. © 2007 Society of Chemical Industry.